(untitled) (Journal of Medicine, 2013)
Leukemia cutis is not a common manifestation of leukemia but when present it indicates poor prognosis. Here we report a case of an atypical presentation of acute myeloblastic leukaemia who presented with neurological features and skin eruption. DOI: http://dx.doi.org/10.3329/jom.v14i1.14587 J MEDICINE 2013; 14 : 91-93